Sarcoidosis as a diagnostic challenge – a case report - V. O. Shuper; S. V. Trefanenko; S. V. Shuper; D. A. Trefanenko (Zaporožskij Medicinskij Žurnal)
Sarcoidosis is considered a disease of unknown etiology which usually affects several organs and systems of the body and is manifested by the development of non-caseous granulomas. It is predominantly a multisystemic granulomatous disease that most often affects the respiratory and lymphatic systems, but varies clinically from patient to patient, making it difficult to diagnose correctly. The diagnosis is based on clinical and radiological data, the results of the sarcoidosis biomarker examinations, confirmed by the histological picture of non-caseous epithelioid cell granulomas. The use of modern instrumental methods of examination such as magnetic resonance imaging, high-resolution computed tomography, 18F-fluorodeoxyglucose-positron emission tomography has significantly improved the diagnosis of sarcoidosis.